DIPLOMASI INDONESIA DALAM MENYELESAIKAN SENGKETA DUMPING PRODUK MINYAK ALKOHOL (FATTY ALCOHOLS) INDONESIA-UNI EROPA DI BADAN WTO PERIODE 2010-2018 - Ersa Mayori Raharjo, - (2018)
Indonesia's Diplomacy in Resolving the Dumping Dispute on Indonesian Alcohol Oil Products - The European Union at the WTO Agency is an attempt to find solutions to clarify and resolve misunderstandings of understanding between two related parties, in this case Indonesia and the European Union. The existence of different views of corporate systems adopted in both countries make the problem and cause the loss is material and inmateril. Dumping is the focus of this research is an example of one of the problems of cooperation between two related parties, so to finish it usually will be completed in a body, in this case the responsible body is the WTO. The Thinking Framework of this research uses the theory of Diplomacy, Negotiation Theory and Concept of Dumping and Anti-Dumping. This research uses descriptive method with qualitative approach type. The results of Indonesian Diplomacy in Resolving the Dumping Dispute on Indonesian Alcohol Oil Products - the European Union in the WTO Agency has resulted in a decision in which the State which is proven to have erred must follow the rules stipulated by the institution and vice versa so that, in the future to experience such problems again, then it has a flow and procedure to facilitate the process of completion